(untitled) (Journal of Informatics and Mathematical Sciences, 2011)
In this paper, I_g-closed sets and I_g-open sets are used to define and investigate a new class of functions called contra I_g-continuous functions in ideal topological spaces. We discuss the relationships with some other related functions.